Expression and significance of cystine transporter SLC7A11/xCT in early colorectal cancer specimens from endoscopic submucosal dissection: Cystine Transporter SLC7A11 in CRC - Zhang, Xiaolei; Wang, Chunhui; Yan, Zhe; Kong, Xianyi (Cellular and Molecular Biology, 2024)
The SLC7A11/xCT cystine transporter is intricately linked with ferroptosis. By mediating intracellular cystine flux, it regulates oxidative stress within neoplastic cells, thereby curtailing ferroptosis and influencing the emergence of colorectal cancer. This study aimed to gauge the SLC7A11/xCT expression across various tumorigenic stages in early colorectal adenocarcinoma tissues, shedding light on its specific role in the genesis of these early malignancies. Sixty specimens that underwent endoscopic submucosal dissection (ESD) resection with pathologic diagnosis of colorectal adenocarcinoma were collected. SLC7A11/xCT expression was pinpointed using immunohistochemistry, and correlations with the patients' clinical-pathological features were drawn. Additionally, a comprehensive bioinformatics assessment was undertaken to discern differential SLC7A11/xCT expressions across a spectrum of cancers. Immunohistochemical assessments unveiled a pronounced cytoplasmic SLC7A11/xCT expression, manifesting as a brownish-yellow hue, particularly in nascent colorectal cancer samples. Its expression was discernibly correlated with both patient gender and adenocarcinoma differentiation grade (P<0.05). Nevertheless, factors such as patient age, tumor localization, infiltration depth, diameter, adjacent adenoma histology, its major axis, and dysplasia degree bore no statistical significance with SLC7A11/xCT levels (P>0.05). Bioinformatics insights pointed to an upregulated SLC7A11/xCT expression across diverse malignancies, inclusive of colon adenocarcinoma, esophageal cancer, acute myeloid leukemia, lung squamous cell carcinoma, colorectal cancer, and endometrial cancer (P<0.05). Elevated SLC7A11/xCT expression marks early colorectal adenocarcinoma, with the intensity of this expression being intertwined with the patient's gender and the tumor's differentiation grade. It is postulated that colorectal cancer cells might amplify SLC7A11/xCT to stymie ferroptosis, thus fostering neoplastic proliferation, metastasis, and cellular stemness.